The dark side of doing good: a qualitative study to explore perceptions of local healthcare providers regarding short-term surgical missions in Port-au-Prince, Haiti - Merrill Chaus (Inishmore Laser Scientific Publishing Ltd, 2020)
## Background In response to the increasing global burden of surgical diseases, medical providers from high-income countries are increasingly volunteering in underserved regions. Short-term surgical missions are growing in number but lack appropriate oversight. Many studies on volunteers' perspectives have been published, but few have examined the perspectives of local healthcare providers. ## Aim To explore perceptions of Haitian healthcare providers regarding short-term volunteer missions in order to identify positive and negative perceptions. ## Methods A qualitative approach utilizing interpretivist epistemology and a social constructivist perspective captured perceptions of participants in their social setting. Interpretivism recognizes that perceptions are subjective and socially constructed. After purposive sampling, 17 participants were recruited. In-depth recorded interviews with assistance from local interpreters explored participants' perceptions. Using thematic content analysis, unexpected themes emerged. ## Results Four themes emerged: general perceptions, perceived effect on healthcare system, perceived effect on healthcare workers, and future recommendations. In general, local healthcare workers appreciate the skills and knowledge that teams impart and the improved access to surgical services for the poor. However, volunteers working independent of local teams create negative perceptions, stress local healthcare providers, and strain hospital resources. Future teams should utilize local perceptions to measure impact and effectiveness of their efforts. ## Conclusions Perceived impact of short-term surgical missions is dependent on participant perspective. This study addresses negative perceptions and offers recommendations for before, during, and after a mission. Surgical missions that emphasize training local staff and forming long-term relationships have a greater impact on surgical capacity than do missions that focus primarily on surgical volume. Further research on local perceptions is essential to ensure that local voices continue to be heard and that altruistic efforts of volunteers do not inadvertently cause negative effects.